Technology-Enhanced Role-Playing in Experiential Historical Learning: Fostering Elementary Students’ Nationalism Attitudes - Made Ayu Cantika Velicia Dewi; I Gusti Agung Ayu Wulandari; A. A. Ayu Dewi Sutyaningsih (Universitas Pendidikan Ganesha, 2026)
Nationalism is an essential character value that should be developed from elementary school because it relates to identity, love for the country, historical awareness, and social responsibility. However, historical learning in IPAS is often dominated by teacher-centered methods, limiting participation, empathy, and value internalization. This study aimed to analyze the effect of technology-enhanced role-playing in experiential historical learning on students’ nationalism attitudes in the Rengasdengklok Event. A quantitative approach was employed using a quasi-experimental design with a non-equivalent control group. The sample consisted of 60 sixth-grade students in Cluster III, North Kuta District, Bali, divided into 31 students in the experimental group and 29 students in the control group. Data were collected using a nationalism attitude observation sheet containing 20 dichotomous Yes/No items covering love for the country, willingness to sacrifice, unity, responsibility, and pride. Data were analyzed using descriptive statistics, prerequisite tests, and an independent-samples t-test. The results showed that the experimental group obtained significantly higher nationalism attitude scores than the control group. Technology-enhanced role-playing enabled students to understand historical contexts through digital stimuli, portray figures, collaborate, and reflect on struggle values. These findings confirm its effectiveness as an interactive learning strategy for strengthening students’ nationalism attitudes.